2020
DOI: 10.5761/atcs.ra.19-00170
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diabetes Mellitus on Prognosis of Patients with Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Purpose: To quantitatively evaluate the effect of preexisting diabetes mellitus (DM) on the outcomes of patients with non-small-cell lung cancer (NSCLC). Materials and Methods: Observational studies comparing the prognosis of NSCLC patients with and without diabetes were identified from PubMed, EMBASE, and The Cochrane Central Register of Controlled Trials (CENTRAL). We searched for studies that published in English from inception to March 30, 2019, using search terms related to diabetes and NSCLC. Pooled haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
(112 reference statements)
2
19
0
Order By: Relevance
“…Significant overlap occurs between symptoms of these diseases and lung cancer, including cough, dyspnea and chest tightness [44]. Another common comorbidity, unrelated to tobacco use, was diabetes, sharing the same risk factors with lung cancer, such as age, diet and smoking [36,45]. Our findings highlight the most prevalent comorbidities among lung cancer patients and the pattern of correlations between the most common comorbidities.…”
Section: Discussionmentioning
confidence: 69%
“…Significant overlap occurs between symptoms of these diseases and lung cancer, including cough, dyspnea and chest tightness [44]. Another common comorbidity, unrelated to tobacco use, was diabetes, sharing the same risk factors with lung cancer, such as age, diet and smoking [36,45]. Our findings highlight the most prevalent comorbidities among lung cancer patients and the pattern of correlations between the most common comorbidities.…”
Section: Discussionmentioning
confidence: 69%
“…At the level of cysts, 34 out of 61 cysts (55.7%) were in the left lung, and most of the cysts occurred in the left lower lobe (42.6%). This contrasts with studies that found more right lung involvement, most commonly in the right lower lobe, either in studies that excluded giant cysts [ 7 ], or those that included them [ [13] , [14] , [16] , [17] ]. Onal et al [ 7 ] investigated the relation between cyst location and rupture in pediatrics and they excluded patients with multiple cysts in one lung.…”
Section: Discussionmentioning
confidence: 79%
“…According to Usluer et al, giant cysts have a higher tendency for rupture, which is a dangerous complication and can lead to anaphylaxis or suffocation [ 4 , 12 ]. Giant cysts usually result from delayed diagnosis or treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to discuss the role of comorbid diabetes where RAGE expression is increased (Kay et al, 2016) and its impact on cancer outcomes. In non-small cell lung cancer, patients with comorbid diabetes experience lower survival rates (Bi et al, 2020) and poorer outcomes following lung resection (Komatsu et al, 2020). These observations appear consistent across a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%